(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article explores the sociology of punishment as a transformative direction in modern state criminal policy. Moving beyond traditional penological paradigms, it analyzes punishment as a complex social institution shaped by historical, economic, and cultural forces, synthesizing theories from Durkheim, Marx, Foucault, Elias, and Garland. Based on international experiences and humanistic reforms in New Uzbekistan, the study highlights the ineffectiveness of mass incarceration and advocates for the decriminalization of minor offenses, the use of alternative sanctions, and the resocialization of offenders.